2012
DOI: 10.1161/circulationaha.112.094359
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Exposure of Healthy Young Volunteers to Ozone Causes Cardiovascular Effects

Abstract: Background— Recent epidemiology studies have reported associations between short-term ozone exposure and mortality. Such studies have previously reported associations between airborne particulate matter pollution and mortality, and support for a causal relationship has come from controlled-exposure studies that describe pathophysiological mechanisms by which particulate matter could induce acute mortality. In contrast, for ozone, almost no controlled-human-exposure studies have tested whether ozone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 46 publications
12
114
0
Order By: Relevance
“…Inhalation of oxidant gases and other pollutants can compromise cardiac function (28). Inhalation of environmentally persistent free radicals, potentially derived from combustion of chlorine-containing hydrocarbons in rats, also caused cardiac inflammation and loss of function (29).…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of oxidant gases and other pollutants can compromise cardiac function (28). Inhalation of environmentally persistent free radicals, potentially derived from combustion of chlorine-containing hydrocarbons in rats, also caused cardiac inflammation and loss of function (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, subjects were recruited under an Environmental Protection Agency contract with Westat Corporation (Rockville, MD). Cardiac and pulmonary function, and systemic effects of ozone on coagulation and inflammatory markers have been previously reported from this study (25). A total of 24 volunteers were involved in the study.…”
Section: Methods Original Study Design: Study Population and Ozone Exmentioning
confidence: 84%
“…During each visit, the subjects were exposed to either 0.3 parts per million ozone or filtered air for 2 hours in the morning time in a blinded manner. During the exposure, subjects alternated between 15 minutes of rest and 15 minutes of exercise on a cycle ergometer (25). Exposures were conducted at the U.S. Environmental Protection Agency, Human Studies Facility on the campus of the University of North Carolina, Chapel Hill.…”
Section: Methods Original Study Design: Study Population and Ozone Exmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,34,35 Epidemiologic studies of short-term air pollution exposures have also consistently demonstrated relationships with both airway and systemic infl ammation in healthy individuals. [36][37][38] Whether longer-term exposures result in fi brosis in humans remains unknown.…”
Section: Potential Mechanismsmentioning
confidence: 99%